Ultra-small gold nanoparticles immobilized on mesoporous silica/graphene oxide as highly active and stable heterogeneous catalysts1. Issue 21 (14th March 2015) - Peng, Li; Zhang, Jianling; Yang, Shuliang; Han, Buxing; Sang, Xinxin; Liu, Chengcheng; Ma, Xue; Yang, Guanying
<x xml:space="preserve">Abstract</x> The ultra-small gold nanoparticles immobilized on the mesoporous SiO2/graphene oxide (GO) support were formed via a one-pot synthetic route.